The Role of Brainware in Educational Management Information Systems - Filma Muhazri Sembiring; Amiruddin Amiruddin; Tia Pratiwi; Salisa Afany; Candra WinataCandra Winata (Universitas Muhammadiyah Enrekang, 2023)
Education Management Information System (MIS-Education) is an information system used to facilitate the collection, processing, storage and use of data and information in education management. SIM-Education aims to increase the efficiency and effectiveness of education management through the use of integrated information technology and information systems. In the educational information system there is an element of brainware, where this brainware is an important element in the implementation of an education management information system (MIS-Education). Brainware is a term used to describe the human resources involved in the development, operation and use of information systems. The role of brainware in SIM-Education is very important because brainware plays a key role in managing a quality information system. In this case, brainware must have the appropriate skills and competencies to manage and utilize SIM-Education effectively. The purpose of this study is to find out how brainware plays a role in educational management information systems. The method used in this research is library research. The result of this study is that the role of brainware is very important in educational management information systems. The quality of the brainware involved in the implementation of an education management information system will greatly affect the success of the system. Therefore, it is necessary to develop the quality of the brainware involved in managing the education management information system.